Unnatural death [large type] - Cornwell, Patricia Daniels (Cornwell, Patricia Daniels. Scarpetta series, 2023)
Two mauled bodies in the woods. Top secret autopsies. The most chilling cases of Scarpetta's career. In this thrilling new installment of Patricia Cornwell's #1 bestselling Scarpetta series, chief medical examiner Dr. Kay Scarpetta finds herself in a Northern Virginia wilderness examining the remains of two campers wanted by federal law enforcement. The victims have been savaged beyond recognition, and other evidence is terrifying and baffling, including a larger-than-life footprint. After one of the most frightening body retrievals of her career, Scarpetta must discover who would commit murders this savage, and why.